Study of Apparatus and Methods of Research and Assessment of the Quality and Performance of Combine Knives within the Energy Mining Industry from Romania - Sorina D. Stanila; Adriana Zamora; Daniel N. Fita; Mila Ilieva Obretenova (Science and Technology - Recent Updates and Future Prospects Vol. 3, 2024)
The sustainable development of mining processes requires a deep knowledge of the effectiveness of mining equipment and is quite complex to analyze due to the intrinsic characteristics of the mining industry. In this regard, its measurement and control can lead to appropriate management, improving the mining processes’ efficiency, increasing safety levels, and reducing environmental impacts. From the practice of using combine harvesters in mining, a fairly high consumption of knives used was observed. From this point of view, a number of studies have been conducted on various tests that have undergone combined knives, such as cutting tests, wear tests, and tests of shock. The equipment with which these tests were carried out allowed the investigation of the rock extraction process with a full range of dislocation tools to describe the working conditions of a certain type of rock and to determine the optimal configuration of cutting tools. In order to research the quality and performance of cutting tools, this paper aims, to present the methods of analysis of predictive reliability and present some methodologies, namely the existing equipment for this purpose. Laboratory and underground results have allowed the study of the applicability of classical dislocation tools, as well as the selection of the most effective.